Level of Teachers’ Skills in the Implementation of al-Quran Teaching Formative Assessment in Religious Schools in Brunei Darussalam - Untong, Roslan; Jemali, Misnan; Abu Bakar, Norwati (Journal of Social Transformation and Regional Development, 2021)
Formative assessment in the teaching of the Qur’an is important to build a comprehensive and continuous potential to master the reading of the Qur’an among religious school students. However, the problem that exists is the extent to which teachers’ skills in implementing formative assessment of Quranic teaching in religious schools in Brunei Darussalam. The objective of this study is to examine the skills of teachers in implementing Formative Assessment of Quranic teaching in religious schools in NBD. This study uses quantitative methods using a questionnaire involving a total of 201 teachers from 37 religious schools in Brunei Darussalam. The findings of this study show that Quran teachers in religious primary schools in Brunei Darussalam have moderately high skills (mean = 3.83) in terms of teacher skills related to the concept of formative assessment. This data shows that the skills of teachers in formative assessment during Teaching and learning al-Quran in terms of giving feedback to improve student learning in al-Quran is high (mean = 3.83). While the aspect of teacher skills related to planning formative assessment activities to be applied in the process of teaching and learning al-Quran is low but still at a moderately high level (mean = 3.26). This study presents an important finding that shows the efforts that have been carried out by the Department of Islamic Studies and District Islamic Studies Officers by providing skills to religious school teachers with courses related to strong basic concepts in the formative assessment required by teachers- Quran teacher, to be able to distinguish between formative and summative practices. In conclusion, this study found that overall, the level of teachers’ skills in formative assessment during the implementation of Quranic teaching is at a moderately high level.